THE EFFECTIVENESS OF USING ARRANGING WORD CARD BY LOOKING PICTURE IN TEACHING PRESENT CONTINUOUS TENSE AT SMPN 3 RANTEPAO SATAP - Mangende’, Natalia (Publikasi dan UKI Press UKI Toraja., 2020)
The purpose of this study was to find out the effectiveness media of word card by looking picture in improving students' understanding in learning Present Continuous Tense at SMPN 3 Rantepao Satap. In analyzing the data of this research, the writer employed quantitative method. The subjects of this study were 21 students of SMPN 3 Rantepao Satap. Research data were collected by providing teaching and testing. The data collected was obtained in obtained three steps namely pre-test, treatment and post-test and the analyzed using SPSS program. The results of this study prove a fact in teaching the Present Continuous Tense in grade 8 of SMPN 3 Rantepao Satap. It can be seen from the scores obtained from the pre-test and post-test. The results of the data analysis in this study showed that the t-test value was higher than the t-table with a significance level of 0.05% (0.05), namely (18.283 > 1.725). it can also be seen from the significance of the paired sample t-test, which is 0.001 smaller than 0.05 (0.001 < 0.05).